9(3n-4)=(7n+4)+1

Simple and best practice solution for 9(3n-4)=(7n+4)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3n-4)=(7n+4)+1 equation:


Simplifying
9(3n + -4) = (7n + 4) + 1

Reorder the terms:
9(-4 + 3n) = (7n + 4) + 1
(-4 * 9 + 3n * 9) = (7n + 4) + 1
(-36 + 27n) = (7n + 4) + 1

Reorder the terms:
-36 + 27n = (4 + 7n) + 1

Remove parenthesis around (4 + 7n)
-36 + 27n = 4 + 7n + 1

Reorder the terms:
-36 + 27n = 4 + 1 + 7n

Combine like terms: 4 + 1 = 5
-36 + 27n = 5 + 7n

Solving
-36 + 27n = 5 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
-36 + 27n + -7n = 5 + 7n + -7n

Combine like terms: 27n + -7n = 20n
-36 + 20n = 5 + 7n + -7n

Combine like terms: 7n + -7n = 0
-36 + 20n = 5 + 0
-36 + 20n = 5

Add '36' to each side of the equation.
-36 + 36 + 20n = 5 + 36

Combine like terms: -36 + 36 = 0
0 + 20n = 5 + 36
20n = 5 + 36

Combine like terms: 5 + 36 = 41
20n = 41

Divide each side by '20'.
n = 2.05

Simplifying
n = 2.05

See similar equations:

| 9-2x-7=6x+4-2x | | -75-k=195 | | 2(3k-1)/5+4=3k | | x+54=4x | | (6+2x)(3+3x)=8 | | 111118n^2+60n+50=0 | | 2(3k-1)/5+4=3k(5) | | a+10=67 | | (2x^2+7x)-(x^2-6x-2)= | | 5x^2+20x+31=0 | | p+50=149 | | 2x-56=14 | | 10p(3s)= | | 9(3n-4)=(7n+4)1 | | 25y^2-144=0 | | 22=-4p-10 | | 10p(3s+10p)= | | n-14=92 | | 4+6p-6p=p-2 | | m+20=30 | | x^2+6x+5=9 | | 3y+19=47+2y | | 3/7H=-18 | | 5(6x+2)+6=30x+16 | | 5y=12y+20 | | 2+7(10+15k)= | | .8x-2.9=.3 | | -x^2=-4x | | 3x-5x=8x | | x-(8-3x)=2(3x+5) | | 3m^2+30m+75= | | 8-(2n-6)=2-3n |

Equations solver categories